Prophylactic Heme Arginate Infusion for Acute Intermittent Porphyria - Kuo, Hung-Chou; Lin, Chia-Ni; Tang, Yi-Fen (Frontiers in Pharmacology, 2021)
Objectives: This study aimed to evaluate the efficacy of long-term weekly prophylactic heme arginate (HA) infusions in reducing attack frequency and severity in female AIP patients. Methods: We report the results of five female AIP patients with frequent recurrent attacks (>9/year) before and after institution of weekly prophylaxis with heme arginate (3 mg/kg body weight). All five cases had confirmed disease-associated mutations in the porphobilinogen deaminase gene, and all had received genetic and clinical counseling about AIP. Results: In the five included patients, average annual attack rate (AAR) in the year prior to HA prophylaxis was 11.82 (range 9.03–17.06), and average total HA usage was 32.60 doses (range: 13.71–53.13). After 2.58–14.64 years of HA prophylaxis, average AAR was reduced to 2.23 (range 0.00–5.58), and attack severity (i.e., doses required per attack) was reduced from 2.81 to 1.39 doses/attack. Liver and renal function remained stable during weekly administration of HA prophylaxis. The most common complications were port-A catheter-related events. No other complications or safety concerns occurred with long-term use of HA prophylaxis. Conclusion: Our study demonstrated women with AIP receiving weekly prophylactic HA infusions resulted in fewer episodes that required acute HA treatment while maintaining stable renal and liver function. Weekly prophylactic HA infusions effectively prevent frequent porphyric attacks and reduce attack severity.